Ophthalmological manifestations of Lyell's syndrome (clinical case) - Aleksandr V. Surov; Ekaterina A. Kalizhnikova (LLC "MEDIAFORMAT", 2023)
The paper presents a clinical case of treatment of a patient with ophthalmological manifestations of Lyell's syndrome. Possible therapy options are considered.